2020
DOI: 10.1590/0034-7167-2019-0522
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and body image of patients with urinary disorders

Abstract: Objective: to assess the quality of life and body image of men with difficulty urinating and indwelling urinary catheter users, integrating the socio-demographic, economic and morbidity variables. Method: a cross-sectional analytical study with 64 male patients with urinary problems. Three questionnaires were used for data collection: one containing sociodemographic, economic and morbid data, the Medical Outcome Study 36-item short-form health survey to analyze quality of life, and the Body Dysmorphic Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Furthermore, this study found that formal education level (i.e., patients who attained no formal education and/or primary education) was associated with the development of complications among participants with long-term IUC. This observation was also reported in previous studies [1,6,32,37,38]. Lack or little formal education means lacking the knowledge of general hygienic measures that aims at preventing and controlling infectious diseases, such as UTI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, this study found that formal education level (i.e., patients who attained no formal education and/or primary education) was associated with the development of complications among participants with long-term IUC. This observation was also reported in previous studies [1,6,32,37,38]. Lack or little formal education means lacking the knowledge of general hygienic measures that aims at preventing and controlling infectious diseases, such as UTI.…”
Section: Discussionsupporting
confidence: 84%
“…Complications of indwelling urinary catheterization (IUC) affect patients' well-being, mostly physically, psychologically and socially [1]. Common complications documented in several studies include catheter blockages, leakage, urethral hemorrhage, urethritis, bladder spasms, bladder calculi, vesicoureteral reflux and over the years bladder cancer [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of gastrointestinal, urinary, cardiovascular, and thermoregulation disorders significantly impacted emotional well-being, daily activities, and bodily discomfort [38]. Amaral et al [39] reported a decrement in emotional and social aspects of quality of life among patients with urinary disorders. The collapse of self-image resulting from a loss of independence, particularly regarding the ability to urinate and defecate, could contribute to increased feelings of helplessness and hopelessness.…”
Section: Discussionmentioning
confidence: 99%